2015
DOI: 10.4314/as.v12i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graded dietary levels of Garcinia Kola seed meal on performance, intestinal microbial load, haematological and serum biochemical profile of rabbits.

Abstract: Effect of dietary Garcinia kola seed meal (GKSM) (bitter kola) on the performance, microbial activities and blood constituents of rabbits were investigated. Four rabbit grower mash were prepared such that diet T 0 (control) contained no Garcinia kola seed meal while diets T 1, T 2 and T 3 contained 2.5%, 5.0% and 7.5% Garcinia kola seed meal, respectively, partly replacing maize. Each diet was fed to a group of 9 grower rabbits for 56 days, in completely randomized design (CRD) experiment. Each group was furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
4
1
Order By: Relevance
“…We observed that GKSM used in this study exhibited high hypolipidemic activity at higher inclusion levels of 3% and 4.5% than the control and 1.5% dietary groups (Table-6). Our results do not align with the reports of Esiegwu et al [31] who did not record any treatment effect on serum cholesterol on feeding rabbits with GKSM.…”
Section: Serum Biochemical Parameterscontrasting
confidence: 99%
See 4 more Smart Citations
“…We observed that GKSM used in this study exhibited high hypolipidemic activity at higher inclusion levels of 3% and 4.5% than the control and 1.5% dietary groups (Table-6). Our results do not align with the reports of Esiegwu et al [31] who did not record any treatment effect on serum cholesterol on feeding rabbits with GKSM.…”
Section: Serum Biochemical Parameterscontrasting
confidence: 99%
“…Ebenebe et al [51] reported that as the dietary inclusion levels of G. kola increased from 2.5% to 7.5%, the weight gain of the rabbits was significantly depressed. Higher levels of GKSM had been previously reported to have growth-depressing effects on rabbits [31,52] and broiler birds [30]. The growth-depressing effects of higher GKSM may be due to the presence of tannins and oxalate.…”
Section: Growth Performance Indicesmentioning
confidence: 86%
See 3 more Smart Citations